Cost-effectiveness of semaglutide 2.4 mg versus liraglutide 3 mg for the treatment of obesity in Greece - Papantoniou, Panagiotis; Maniadakis, Nikolaos (Frontiers in Public Health, 2025)
BackgroundObesity is a major public health issue associated with significant humanistic and economic burden. In Greece, liraglutide 3.0 mg is currently the only reimbursed pharmacotherapy for obesity, restricted to patients with morbid obesity and selected comorbidities. Semaglutide 2.4 mg has demonstrated superior clinical efficacy in the STEP-8 clinical trial; however, its cost-effectiveness relative to liraglutide requires further investigation to ensure informed reimbursement decision-making.MethodsA state-transition model was developed in Microsoft Excel to evaluate the long-term cost-effectiveness of semaglutide 2.4 mg compared with liraglutide 3.0 mg in adults with obesity (BMI ≥ 35 kg/m2 and ≥ one weight-related comorbidity). Clinical efficacy and safety inputs were derived from the STEP 8 trial, while cost inputs (expressed in 2025 euros) and utility values were obtained from the literature and published local sources. The analysis was conducted over a 40-year time horizon, with both costs and outcomes discounted at an annual rate of 3.5%. Health outcomes were reported as life-years (LYs) and quality-adjusted life-years (QALYs). The evaluation was conducted from the perspective of the Greek third-party payer, and deterministic, scenario, and probabilistic sensitivity analyses were performed.ResultsSemaglutide 2.4 mg was associated with an incremental mean increase in quality-adjusted life expectancy of 0.09 at modestly incremental higher costs of 1,083 compared with liraglutide 3.0 mg, yielding an incremental cost-effectiveness ratio (ICER) of €12,724 per QALY gained, below the willingness-to-pay threshold of €27,117. Probabilistic sensitivity analysis showed semaglutide dominated liraglutide in 80.8% of simulations (greater QALYs and lower costs) and reached 100% probability of cost-effectiveness at a willingness-to-pay threshold of €9,000 per QALY. Deterministic and scenario analysis identified treatment duration, time horizon, discount rates, and diabetes-related complication costs as key drivers of ICER variability.ConclusionsSemaglutide 2.4 mg is likely to be a cost-effective treatment option compared to liraglutide 3 mg for patients with a BMI ≥ 35 and at least one weight-related comorbidity in Greece.